Tropical Pines in Orissa - Das, B. L. (Indian Forester, 1982)
The paper summarises the experiences of growing tropical pines in the State of Orissa tried at elevations between 700 to 950 m. The main species tried are Pinus kesiya, P. caribaea (all three varieties), P.oocarpa and P. patula among some others like P. rediata etc. It has been shown that P. caribaea is the most suitable species followed by P. kestya. The performance of P. patula and P.oocarpa needs further observation while P. radiata should not be tried further. Among the P. carlbaea varieties, the hondurensis variety shows fastest growth followed by var. bahamensis and var. caribaea. Though at higher altitudes Daringabadi (945 m) var. bahamensis may show better growth. However. the form exhibited by var. hahamensis is consistently and uniformly superior followed by var. caribaea; var. hondurensis shows great variation with many individuals of poor form. The author has made a strong plea for selecting better stands is the natural forests of P. kesiya in Meghalaya etc. and start a programme on genetic improvement as this species holds promise if stem form could be improved.